2015
DOI: 10.1089/mdr.2015.0020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Community- and Healthcare-Associated Methicillin-Resistant Staphylococcus aureus Isolates in Southern Taiwan

Abstract: A growing tendency for community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) to be involved in nosocomial infections was reported. The predominance of SCCmec type IV or V CA-MRSA in soft tissue infection has also been indicated in Northern Taiwan. To establish basic information about the molecular characteristics of MRSA in our region, a total of 102 MRSA isolates were collected and characterized by an array of typing methods. Healthcare-associated MRSA (HA-MRSA) were found to be more resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(28 reference statements)
3
5
0
Order By: Relevance
“…According to the previous reports [ 18 ], HA-MRSA is usually detected with SCC mec type I, II, and III; in contrast, CA-MRSA is reported as carrying type IV and V. In this study, SCC mec III was the dominant type in HA-MRSA strains (87.3 %), also the main type of CA-MRSA (60.9 %). This study confirms that CA-MRSA clones partially carry the SCC mec type III and SCC mec type I, as reported in a recent study in Guangzhou [ 16 ].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…According to the previous reports [ 18 ], HA-MRSA is usually detected with SCC mec type I, II, and III; in contrast, CA-MRSA is reported as carrying type IV and V. In this study, SCC mec III was the dominant type in HA-MRSA strains (87.3 %), also the main type of CA-MRSA (60.9 %). This study confirms that CA-MRSA clones partially carry the SCC mec type III and SCC mec type I, as reported in a recent study in Guangzhou [ 16 ].…”
Section: Discussionsupporting
confidence: 55%
“…SCC mec typing of MRSA strains was conducted by multiplex PCR method as previously described [ 13 ]. The genetic relationship of the isolates was determined by PFGE as previously described [ 18 ]. Cluster analysis was performed with the software program BioNumerics 5.0 (Maths, Belgium) using the Dice coefficient and the unweighted pair group method (UPGMA).…”
Section: Methodsmentioning
confidence: 99%
“…Another striking finding in this study was that 11 CA‐MRSA (47.8%) and 7 HA‐MRSA (35%) harboured the gene for PVL toxin (Table ). Although PVL is known as a common virulence factor of CA‐MRSA and HA‐MRSA strains seldom carry this gene, several studies in Taiwan (Lee et al., ) and USA (Zetola, Francis, Nuermberger, & Bishai, ) showed that their HA‐MRSA isolates had a considerable rate of PVL positivity in their regions supporting the hypothesis that PVL is not the sole marker for recognizing a community lifestyle, but rather one of several important factors that may play a key role in the successful dissemination of CA‐MRSA (Zhang, McClure, Elsayed, Tan, & Conly, ). Our above findings confirm that the CA‐ and HA‐MRSA classifications are no longer distinct and the boundaries between HA‐ and CA‐MRSA are becoming increasingly difficult.…”
Section: Discussionmentioning
confidence: 96%
“…Some recent studies report SCCmec type III as the most frequent type isolated from hospital-acquired infections. This can be explained as the studies conducted on the MRSA strains mostly isolated from nosocomial infections, as the present study [12,13].…”
Section: Discussionmentioning
confidence: 77%
“…De Oliveira et al [12] reported the most frequent cassette as SCCmec type II with a rate of 53.7% amongst 123 Staphylococcus aureus strains. Lee et al [13] found the most frequent type as type I (8.7%) amongst the community-acquired cases, and as type V (24.4%) amongst the hospital-acquired isolates.…”
Section: Discussionmentioning
confidence: 97%